2018
DOI: 10.1101/300889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of 12 genetic loci associated with human healthspan

Abstract: The mounting challenge of preserving the quality of life in an aging population directs the focus of longevity science to the regulatory pathways controlling healthspan. To understand the nature of the relationship between the healthspan and lifespan and uncover the genetic architecture of the two phenotypes, we studied the incidence of major age-related diseases in the UK Biobank (UKB) cohort. We observed that the incidence rates of major chronic diseases increase exponentially. The risk of disease acquisitio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…The latter was supported by a significant association between P C 1 and the log-linear proportional incidence of chronic age-related diseases risk estimate in the UKB dataset. These findings corroborate the findings investigating the GWAS of healthspan [18], where at least some of the genetic variants associated with longer healthspans were found to predict both lifespan and the incidence of specific age-related diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The latter was supported by a significant association between P C 1 and the log-linear proportional incidence of chronic age-related diseases risk estimate in the UKB dataset. These findings corroborate the findings investigating the GWAS of healthspan [18], where at least some of the genetic variants associated with longer healthspans were found to predict both lifespan and the incidence of specific age-related diseases.…”
Section: Discussionsupporting
confidence: 89%
“…BAA also turned out to be a significant risk factor for the prospective incidence of chronic related diseases. Following [18], we observed that there is a large cluster of age-related diseases, such as cardiovascular diseases (coronary heart disease, heart attack, heart failure, stroke), diabetes, hypertension, and cancer. All the diseases from the list are characterized by an exponentially increasing probability of incidence, with a doubling time similar to that of the mortality rate of eight years identified in the Gompertz mortality law in human population.…”
Section: Biological Age Acceleration Predicts Mortality and The Incidmentioning
confidence: 99%
“…Aging in most species, including humans, manifests itself as a progressive functional decline leading to increasing prevalence (Mitnitski andRockwood 2016, Yu et al 2017) and incidence of the chronic age-related diseases, such as cancers, diabetes, cardiovascular diseases (Niccoli and Partridge 2012, Podolskiy et al 2016, Zenin et al 2019 or disease-specific mortality (Barzilai and Rennert 2012), all accelerating exponentially at a rate compatible with that of the Gompertz mortality law (Gompertz 1820, Makeham 1860). The physiological indices or physiological state variables, such as blood biochemistry or cell count markers change with age in a highly coordinated manner.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of lead SNPs are strongly associated with selfrated health and resilience, in line with the large loadings of these traits in the construction of GIP1 (Figure 3; Supplementary Table 3). Loci near APOE, HLA-DRB1/DQA1, LPA, and CDKN2B/-AS1 have previously been validated using the same trait in an external cohort [2][3][4] . For the remaining 23 loci, we measured lead SNP effects on FinnGen participant survival (Release 5; N = 203,244; 6.94% deceased) and BioBank Japan participant survival (N = 135,983; 24.1% deceased), to provide additional evidence of their association with human ageing traits in independent samples.…”
Section: Characterising the Genomics Of Lifelong Mental And Physical mentioning
confidence: 99%